Expressive Reading as a Means of Improving the Teacher's Communicative Culture - Turaeva Shakhida Egamberdievna (Open Academia, 2023)
Many graduates of pedagogical universities do not go to work at school because they experience communication difficulties in communicating with children. Teaching the art of reading contributes to the improvement of the communicative culture of future teachers, if the teachers of the "Practicum on Expressive Reading" proceed from the understanding of expressiveness not only as a linguistic category, but also as an aesthetic one, which involves influencing the mind, feelings and will of listeners in the process of communicating with them